Challenges in Pediatric Cardiac Anesthesia in Developing Countries - Cvetkovic, Mirjana (Frontiers in Pediatrics, 2018)
Introduction Approximately 90% of a million children worldwide born with congenital heart defect do not have an access to adequate paediatric cardiac care. The World Society for Paediatric and Congenital Heart Surgery, established in 2006 shifted the focus from providing individual paediatric cardiac care to developing global standards for the practice of paediatric cardiac surgery and professional education of the local teams. Materials and Methods After recognising the challenges of the local team regarding providing safe anaesthesia and functioning as a broader team, we have focussed our education on simplifying anaesthetic procedures and advancing structured team approach. The appropriate selection of patients and simplifying anaesthetic technique should be the standard of care. We introduced structured approach to daily education using just in time teaching, case based discussions and simple skill training simulation sessions. Furthermore, we enhanced team-training approach applying tools such as WHO surgical safety checklist and implementation manual, SAFE communication, introducing KDD with SMART aim, SCAMPs, advanced protocols of care and culture change tools. Results Following a significant number of short missions to developing centres we have, within NGO, succeeded to support building and maintaining several local paediatric cardiac centres with structured approach to anaesthesia and team building. Conclusion The appropriate selection of patients is one of the most important contributing factors for decreasing morbidity and mortality rate in paediatric cardiac surgery patients. The anaesthesia technique for paediatric cardiac procedures should be aimed at fast-track surgery, with early extubation as a goal. Regional blocks such as paravertebral and caudal should be considered for perioperative pain control. By introducing structured approach to daily education and by enhancing team-training approach we have contributed evolving sustainable paediatric cardiac centres in developing countries.